Cultivate Growth Mindset via Self-Compassion. - Dudsdeemaytha, Jitra (Saengtham College Journal, 2021)
Mindsets reflect one’s perception and belief of the world positively and negatively. Growth mindset refers to one’s belief that intelligence is a changeable trait, that can be developed with effort and perseverance. However, fixed mindset indicates to one’s belief that intelligence is a stable trait. Everyone has both mindsets depending on which mindset is more dominant in that person. This article aims to enhance growth mindset via self-compassion. In general, when one confronts crisis and obstacle, fixed mindset emerges easier than growth mindset. Learning to soothe oneself using three crucial components of self-compassion; common humanity, self-kindness, and mindfulness, one can create more alternatives to overcome fixed mindset and expand more strategies of growth mindset to embrace the benefits of failure.